Status and Trend of Deaths Due to Traffic Accidents From 2001 to 2010 in Iran - MR Ghadirzadeh; A Shojaei; A Khademi; M Khodadoost; M Kandi; F Alaeddini; S Moradi (مجله اپیدمیولوژی ایران, 2015)
Background & Objectives: The number of road traffic accidents (RTAs) and their mortality are increasing in the world. In Iran, RTAs have caused life losses and economical damages. Death is the most important consequence of the accidents in terms of social, economic, and even political expenditures. This paper reports the statistics of the mortality status in the last decade.